Nitrosative stress and apoptosis in non-anemic healthy rats induced by intravenous iron sucrose similars versus iron sucrose originator - Toblli, Jorge Eduardo (2015)
Iron can both induce and inhibit nitrosative stress. Intracellular iron levels play an important role in nitric oxide (NO•) signaling mechanisms. Depending on various factors, such as the cell's redox state and transition metal levels, NO• generation may lead to lipid peroxidation and DNA damage as well as both anti- and pro-apoptotic effects. Administration of intravenous iron sucrose originator (ISORIG) has been shown not to cause significant tyrosine nitration or significantly increased caspase 3 levels in non-anemic rats. In this study, the potential of several marketed iron sucrose similars (ISSs) to induce tyrosine nitration and caspase 3 expression in non-anemic rats was assessed. Although the physico-chemical properties of most of the analyzed ISSs complied with the United States Pharmacopeia for iron sucrose injection, all ISSs resulted in higher levels of tyrosine nitration and increased the expression of caspase 3 versus ISORIG. Moreover, significant differences were detected in tissue iron distribution between ISORIG- and ISS-treated animals. In general, ISORIG resulted in higher levels of ferritin deposits versus ISSs whereas ISSs showed higher Prussian blue-stainable iron(III) deposits than ISORIG. This result suggests that some iron from ISSs bypassed the tightly regulated pathway through resident macrophages of the liver, spleen and bone marrow thus, ending up in the cellular compartment that favors oxidative and or nitrosative stress as well as apoptosis. The results also confirm that polynuclear iron(III)-oxyhydroxide carbohydrates, such as iron sucrose, cannot be fully characterized by physico-chemical methods alone.